Halalan Sa Gitna ng Pandemiya: Mga Sumbong Kay Kurdapya - Nidea, Eilyn Lamadrid (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
This diary/journal format of my creative essay is selected from my writings chronicling my journey as a writer and cultural worker during the two-year plus COVID-19 pandemic during which I wrote a number of poems, essays, plays, and stories for children gathered under the collective title Zine in Quarantine. Kurdapya is an old name which has fascinated me since childhood, and it’s been the name of my diary since then. I submitted this diary collection with prayers and hope of being selected and getting published to give voice to the sentiments of Kakampinks pertinent to the 2022 national elections, and to share some insights about our struggles and aspirations as Filipinos in the midst of these challenging and uncertain times.